Extracorporeal membrane oxygenation as a support for TGA/IVS with low cardiac output syndrome and pulmonary hemorrhage - Hong,Xiaoyang (2013)
A 15-day-old neonate with complete transposition of the great arteries/intact ventricular septum was admitted with life-threatening hypoxemia and heart arrest. After successful resuscitation, heart beat recovered but blood lactate began to arise and maintained above 15 mmol/L 6 hours later. Emergency arterial switch operation was done at 20 hours after resuscitation. Planned extracorporeal membrane oxygenation support was employed postoperatively. The baby experienced severe pulmonary hemorrhage and severe hypoxemia after weaning from cardiopulmonary bypass, which were treated with extracorporeal membrane oxygenation support.